Experienciando Materiais Manipulativos para o Ensino e a Aprendizagem da Matemática - Murari, Claudemir [UNESP] (My University, 2011)
This paper presents some outcomes from research based on classroom experiences. The main themes are the use of mirrors, kaleidoscopes, dynamic geometry software, and manipulative material considering their possibilities for the teaching and learning of Euclidean and non-Euclidean geometries.
Experiencing manipulative material for the teaching and learning of mathematics
Keywords: Kaleidoscopes; Manipulative material; Mirrors; Software of dinamic geometry